Covid 19: How to feel safe working on the front line—your legal and ethical questions answered. (20th January 2021) - Dyer, Clare
Abstract : The pandemic has presented doctors with legal and ethical challenges around how to treat patients in overstretched health services. Clare Dyer examines some of the key questions